The interplay of intracellular calcium and zinc ions in response to electric field stimulation in primary rat cortical neurons in vitro - Alshawaf, Abdullah J.; Alnassar, Sarah A.; Al-Mohanna, Futwan A. (Frontiers in Cellular Neuroscience, 2023)
Recent pharmacological studies demonstrate a role for zinc (Zn2+) in shaping intracellular calcium (Ca2+) dynamics and vice versa in excitable cells including neurons and cardiomyocytes. Herein, we sought to examine the dynamic of intracellular release of Ca2+ and Zn2+ upon modifying excitability of primary rat cortical neurons using electric-field stimulation (EFS) in vitro. We show that exposure to EFS with an intensity of 7.69 V/cm induces transient membrane hyperpolarization together with transient elevations in the cytosolic levels of Ca2+ and Zn2+ ions. The EFS-induced hyperpolarization was inhibited by prior treatment of cells with the K+ channel opener diazoxide. Chemical hyperpolarization had no apparent effect on either Ca2+ or Zn2+. The source of EFS-induced rise in Ca2+ and Zn2+ seemed to be intracellular, and that the dynamic inferred of an interplay between Ca2+ and Zn2+ ions, whereby the removal of extracellular Ca2+ augmented the release of intracellular Ca2+ and Zn2+ and caused a stronger and more sustained hyperpolarization. We demonstrate that Zn2+ is released from intracellular vesicles located in the soma, with major co-localizations in the lysosomes and endoplasmic reticulum. These studies further support the use of EFS as a tool to interrogate the kinetics of intracellular ions in response to changing membrane potential in vitro.